When the world loved the Filipinos and other essays on Philippine history - Dery, Luis Camara (UST Pub. House, 2005)
"The essays focus on different topics about Philippine history. They show different threads that compose the Philippine past and at the same time highlight the many experiences of the Filipino people through the centuries of their existence. They demonstrate the developments that occurred in the country brought about by the interplay of external stimuli. These many developments and variations in the historical development of the country and its inhabitants substantiate the idea that history is not only an interesting field of study but is also an inexhaustible reservoir of lessons from which the Filipino people could draw upon as they face the many uncertainties of the future."--Introduction.